The Evolution of Mental Health Legislation in South Africa: Towards a Rights-Based Approach - Letitia Pienaar (Laws)
This contribution examines the human rights framework and legislative developments in South Africa on persons with mental illness, revealing that the initial focus of the legislation was on control and detention at the cost of the rights of mental health care users. Presently, under its Constitutional democracy, South Africa has progressive Mental Health Legislation focusing on the rights of mental health care users and the least restrictive means of treatment. The contribution considers the impact of the legislative developments on the human rights of mental health care users. There are, however, challenges with the implementation of the legislation most notably illustrated by the Life Esidimeni disaster where a mass deinstitutionalization project led to the loss of life. South Africa’s revised Mental Health Policy Framework holds a renewed commitment to respect a mental health care user’s right to dignity, integrity, privacy, and freedom of movement. This is one step closer to the realisation of the obligations created by the United Nations Convention on the Rights of Persons with Disabilities (CRPD). The contribution considers the 2018 concluding observations by the United Nations Committee on the Rights of Persons with Disabilities, which lays bare areas where yet further improvement is needed in South Africa to eradicate all forms of discrimination against persons with disabilities and, in particular, persons with mental illness Areas where progress have been made are highlighted. South Africa has made steady progress but needs to intensify its efforts to domesticize the CRPD.